The Influence of Brand Image and Customer Satisfaction on Loyalty and Repurchase: A Study on Samsung Electronics Customers in The Context of E-Waste Issues - Desianti Ramadhan, Putri; Widodo, Arry; Rubiyanti, Nurafni (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study aims to analyze the influence of brand image and customer satisfaction on brand loyalty and repurchase decision among Samsung Electronics consumers in Indonesia, within the context of electronic waste (e-waste) management issues. The phenomenon of increasing global e-waste volume and the low recycling rate in Indonesia encourage electronics companies, including Samsung, to implement sustainability strategies to maintain brand image and customer satisfaction. The research method used is quantitative with a Structural Equation Modeling–Partial Least Square (SEM-PLS) approach. Data were collected through an online questionnaire distributed to 200 Samsung Electronics consumers in Indonesia. The variables in this study include brand image, customer satisfaction, brand loyalty, repurchase decision, and demographics as moderating variables. The results show that brand image and customer satisfaction have a positive and significant effect on brand loyalty and repurchase decision. Furthermore, brand loyalty mediates the influence of brand image and customer satisfaction on repurchase decision. However, demographic factors do not moderate the relationship between brand image and customer satisfaction with brand loyalty. These findings indicate that Samsung's sustainability strategy through its e-waste recycling program plays an important role in strengthening brand image, increasing satisfaction, and encouraging repurchase behavior. This research is expected to provide theoretical contributions to the green marketing and consumer behavior literature, as well as practical recommendations for Samsung brand managers to enhance the effectiveness of sustainability programs in Indonesia.